EFFECT OF FINANCIAL LITERACY ON HOUSEWIVES' FINANCIAL PLANNING - Nurhasanah, Nurhasanah; Anggita Permata Yakup,; Silvia Ekasari,; Donny Dharmawan,; Ufi Rumefi, (Journal of Innovation Research and Knowledge, 2024)
The aim of this research is to analyze effect of financial literacy on housewives' financial planning. This type of research uses descriptive associative research with an ex-post facto approach. The population in this study were housewives in Medan City. Sampling in this study used random sampling. From random sampling, the sample was 50 respondents. Data collection obtained in this research was observation, documentation, and questionnaire. The data analysis tool in this research uses simple linear regression. The research results show that financial literacy is positive and significant in housewives' financial planning.